Virtual element method and permanent magnet simulations: potential and mixed formulations. Issue 10 (23rd March 2021) - Dassi, Franco; Di Barba, Paolo; Russo, Alessandro
Abstract : The methodological background of the virtual element method is presented and applied to model permanent magnets via the Kikuchi formulation, considering both linear and non‐linear magnetic permeability of the ferromagnetic regions. The authors examine several study cases: a permanent magnet in free space, a permanent magnet energising a ferromagnetic core, a four‐pole permanent‐magnet motor. In order to validate the proposed approach, comparisons with both virtual and finite element potential formulations are presented and discussed.